2000
DOI: 10.1152/jn.2000.84.6.2888
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Dependent Ion Channels in CAD Cells: A Catecholaminergic Neuronal Line That Exhibits Inducible Differentiation

Abstract: Cell lines derived from tumors engineered in the CNS offer promise as models of specific neuronal cell types. CAD cells are an unusual subclone of a murine cell line derived from tyrosine hydroxylase (TH) driven tumorigenesis, which undergoes reversible morphological differentiation on serum deprivation. Using single-cell electrophysiology we have examined the properties of ion channels expressed in CAD cells. Despite relatively low resting potentials, CAD cells can be induced to fire robust action potentials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…The CAD cell line was used here as the main model system. These cells derive from mouse brain neurons, and on serum deprivation exhibit a differentiated phenotype with major ultrastructural and electrophysiological features of CNS neuronal cells (Qi et al, 1997;Wang & Oxford, 2000). We found that, whilst CAD cells did accumulate abnormal PrP following treatment with proteasome inhibitors, the formation of aggresomes containing aggregated PrP with true PrP Sc characteristics was only a feature of prion-infected cultures.…”
Section: Introductionmentioning
confidence: 77%
“…The CAD cell line was used here as the main model system. These cells derive from mouse brain neurons, and on serum deprivation exhibit a differentiated phenotype with major ultrastructural and electrophysiological features of CNS neuronal cells (Qi et al, 1997;Wang & Oxford, 2000). We found that, whilst CAD cells did accumulate abnormal PrP following treatment with proteasome inhibitors, the formation of aggresomes containing aggregated PrP with true PrP Sc characteristics was only a feature of prion-infected cultures.…”
Section: Introductionmentioning
confidence: 77%
“…CAD Cells-Catecholamine A-differentiated (CAD) cells were grown at 37°C and in 5% CO 2 (Sarstedt, Newton, NC) in Ham's F-12/Eagle's minimum essential media (Amersham Biosciences), supplemented with 8% fetal bovine serum (Sigma) and 1% penicillin/streptomycin (100% stocks, 10,000 units/ml penicillin G sodium, and 10,000 g/ml streptomycin sulfate) (25). Cells were passaged every 6 -7 days at a 1:25 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…Using the whole cell patch clamp configuration, the effects of LCM on VGSCs in the presence of overexpressed CRMP-2 were examined. CAD cells were chosen, because they 1) provide a background easily amenable to genetic manipulation, 2) are of neuronal origin, and 3) express endogenous tetrodotoxin-sensitive Na ϩ currents (25). Current-voltage relationships in control EGFP or CRMP-2-EGFP-expressing CAD cells were examined by the application of 15-ms step depolarizations ranging from Ϫ70 mV to ϩ80 mV (in ϩ10-mV increments) from a holding potential of Ϫ80 mV (Fig.…”
Section: Lcm Affects Namentioning
confidence: 99%
“…CAD cells were cultured in HAM-F12 with 8% fetal bovine serum (FBS) and 1% penicillin/streptomycin as previously described (Wang and Oxford, 2000). Undifferentiated CAD cells were transiently transfected at 60-80% confluence using Polyfect (Qiagen) for 12 hours following to the manufacturer's instructions for HeLa cells.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%